Can PROMIS measures be used to create subgroups for patients seeking orthopaedic care? - George, Steven Z. (Bone Jt Open, 2021)
AIMS: Patient-reported outcome measures have become an important part of routine care. The aim of this study was to determine if Patient-Reported Outcomes Measurement Information System (PROMIS) measures can be used to create patient subgroups for individuals seeking orthopaedic care. METHODS: This was a cross-sectional study of patients from Duke University Department of Orthopaedic Surgery clinics (14 ambulatory and four hospital-based). There were two separate cohorts recruited by convenience sampling (i.e. patients were included in the analysis only if they completed PROMIS measures during a new patient visit). Cohort #1 (n = 12,141; December 2017 to December 2018,) included PROMIS short forms for eight domains (Physical Function, Pain Interference, Pain Intensity, Depression, Anxiety, Sleep Quality, Participation in Social Roles, and Fatigue) and Cohort #2 (n = 4,638; January 2019 to August 2019) included PROMIS Computer Adaptive Testing instruments for four domains (Physical Function, Pain Interference, Depression, and Sleep Quality). Cluster analysis (K-means method) empirically derived subgroups and subgroup differences in clinical and sociodemographic factors were identified with one-way analysis of variance. RESULTS: Cluster analysis yielded four subgroups with similar clinical characteristics in Cohort #1 and #2. The subgroups were: 1) Normal Function: within normal limits in Physical Function, Pain Interference, Depression, and Sleep Quality; 2) Mild Impairment: mild deficits in Physical Function, Pain Interference, and Sleep Quality but with Depression within normal limits; 3) Impaired Function, Not Distressed: moderate deficits in Physical Function and Pain Interference, but within normal limits for Depression and Sleep Quality; and 4) Impaired Function, Distressed: moderate (Physical Function, Pain Interference, and Sleep Quality) and mild (Depression) deficits. CONCLUSION: These findings suggest orthopaedic patient subgroups differing in physical function, pain, and psychosocial distress can be created from as few as four different PROMIS measures. Longitudinal research is necessary to determine whether these subgroups have prognostic validity. Cite this article: Bone Jt Open 2021;2(7):493–502.